Strategies for effective reuse of waste from abandoned buildings under sustainable development - Chen, Jie; Wu, Hua; Su, Binyu; Li, Weiqing (Frontiers in Materials, 2024)
In the continuous promotion of urbanization, abandoned buildings are a huge challenge in achieving sustainable development. If these abandoned buildings are not properly handled, they will cause a huge burden on society, economy, and the environment. Based on the material flow analysis method, an evaluation index system is constructed for abandoned building resources. A systematic study is conducted on the reuse pathways of its waste. This study focuses on the material flow, reuse pathways, and resource utilization strategies of abandoned construction waste, aiming to improve the reuse efficiency of waste building materials and promote the sustainable development. In the study, indicator design is used to quantify the obstacles to the reuse of construction waste, and social and economic costs are analyzed to ensure the comprehensiveness and scientificity. The experimental results showed that the waste recovery rate under this strategy reached 82.7%, and the resource utilization rate increased by 50.1%. For the obstacles to the reuse of construction waste, the network density reached 0.052, and the concentration of the entire network structure was insufficient, indicating that the current management methods for construction waste reuse have further optimization space. This study effectively promotes the sustainable utilization of abandoned buildings in cities, which is of great significance for improving the quality of urban space and promoting sustainable social development.